1972
DOI: 10.1038/icb.1972.40
|View full text |Cite
|
Sign up to set email alerts
|

IMMUNOLOGICAL SUPPRESSION OF PARASITE REJECTION BY REMOVAL OF SELECTED LYMPHOCYTE POPULATIONS: THE EFFECT OF NEONATAL THYMECTOMY AND ANTI‐THYMOCYTE SERUM ADMINISTRATION ON THE RESISTANCE OF RATS TO INFECTION WITH THE NEMATODE, NIPPOSTRONGYLUS BRASILIENSIS

Abstract: Summary. Neonatally thymectomised rats, infected with IV. brasiliensis, showed significant increases in worm-egg production and parasite survival when compared with sham-thymectomised controls, particularly during the later stages of infection. Treatment of infected rats with rabbit anti-rat thymocyte serum resulted in a highly significant suppression of parasite rejection. The production of reagin-like antibody, directed at antigens of N. brasiliensis, was substantially inhibited in both neonatally thymectomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0
8

Year Published

1972
1972
1989
1989

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 13 publications
1
3
0
8
Order By: Relevance
“…[1968], M iller [1971] and Murray et al [1971], which postulates that the mast cell amine system was necessary for the release of anti-worm antibodies. The present results also show that the antibodymediated first step in worm rejection functions in lactating rats, and support the conclusion that the immunological deficiency responsible for the failure of worm expulsion in lactating rats is due to a defect in the second step of worm expulsion, which is lymphocyte-dependent [D ineen and Kelly, 1972].…”
Section: Mast Cell Infiltration and The 2-step Worm Rejection Mechanismsupporting
confidence: 72%
See 1 more Smart Citation
“…[1968], M iller [1971] and Murray et al [1971], which postulates that the mast cell amine system was necessary for the release of anti-worm antibodies. The present results also show that the antibodymediated first step in worm rejection functions in lactating rats, and support the conclusion that the immunological deficiency responsible for the failure of worm expulsion in lactating rats is due to a defect in the second step of worm expulsion, which is lymphocyte-dependent [D ineen and Kelly, 1972].…”
Section: Mast Cell Infiltration and The 2-step Worm Rejection Mechanismsupporting
confidence: 72%
“…More recent data have shown that antibodies alone cannot cause worm expulsion but only damages the worms and makes them susceptible to the lymphocyte-dependent expulsive step [Jones and O gilvie, 1971;Keller and K eist, 1972;Kelly and D ineen, 1972a, b;Kelly, 1972]. The present results show that damage to the worms which is known to be antibody-mediated [Jones and O gilvie, 1971] has occurred by day 13 when no observable mast cells are present in the in testine in both nulliparous and lactating rats.…”
Section: Mast Cell Infiltration and The 2-step Worm Rejection Mechanismmentioning
confidence: 99%
“…Ansiedlung im Darm und anfangliche Eiausscheidung verliefen bei Infektionen mit N . brasiliensis in neonatal thymektomierten Ratten ungestort, doch verzogerte sich die Wurmelimination bei gleichzeitig verlangerter Eiausscheidung (OGILVIE u. JONES, 1967; KELLY, 1972) bzw. erniedrigten PCA-Titern (WILSON et al, 1967;OGILVIE u. JONES, 1967).…”
Section: B Literaturiibersichtunclassified
“…spiralis in Ratten (GORE et al, 1970 und Mausen (KOZAR et al, 1971; DINETTA MACHNICKA, 1972;LARSH et al, 1972;KOZAR, 1973), mit N . brasiliensis in Mausen (KASSAI et al, 1968) und Ratten (KELLY, 1972) und mit Hymenolepis citelli in Peromyscus maniculatus (WASSOM et al, 1974). Dagegen blieb die Wurmburde bei einmaliger Infektion wie bei Zweitinfektion von Ratten mit Schistosoma mansoni unbeeinfluflt, wahrend alle Untersuchungen uber die Immunelimination von Trichinella spiralis bei Ratten 3 gemessenen Antikorper vermindert waren (MADDISON et al, 1970).…”
Section: B Literaturiibersichtunclassified
“…Mortality from these sources is variable, but several reports exemplify the extent of losses that can be encountered in the rat, such as 10% attributable to surgical procedure, 40% to cannibalism, 25% to 'runting' (Jankovic, Waksman & Amason, 1962;Pinnas & Fitch, ] 966; Kelly, 1972). As well as describing in detail the technique for removal of the thymus in the newborn rat, the present paper places emphasis on certain innovations aimed at minimising this wastage.…”
mentioning
confidence: 95%